ANALISIS PENGARUH LINGKUNGAN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI UKM, PERINDUSTRIAN DAN PERDAGANGAN PROVINSI PAPUA BARAT DAYA - Yunus Kawab; Andi Irwan; Mervin Komber (JURNAL LENTERA BISNIS, 2026)
This study, entitled "Analysis of the Influence of Work Motivation and Compensation on Employee Performance at the Manpower, Transmigration, Energy, and Mineral Resources Office of Southwest Papua Province," is motivated by the importance of employee performance as a determining factor in the success of a government agency in carrying out its public service duties and functions. Work motivation and compensation are two key factors believed to influence employee performance. Work motivation reflects internal and external drives that foster enthusiasm for work, while compensation serves as a form of organizational recognition for employee contributions. The purpose of this study is to analyze the influence of work motivation and compensation on employee performance at the Manpower, Transmigration, Energy, and Mineral Resources Office of Southwest Papua Province. This study used a quantitative approach with a survey method. The population in this study was all employees at the office, with purposive sampling used. Data collection was conducted through a questionnaire designed based on indicators of work motivation, compensation, and employee performance in accordance with relevant theories. The data obtained will be analyzed using validity and reliability tests and multiple linear regression to determine the extent of the influence of work motivation and compensation on employee performance. This research is expected to contribute to the development of human resource management policies within local governments, particularly in efforts to improve employee performance through motivational strategies and fair and proportional compensation. The results of this study show a sig value of 0.028 > 0.05 indicating that the work environment does not have a significant effect on employee performance, and the competency variable with a sig value of 0.000 < 0.05 indicates that the competency variable has a significant effect on employee performance and simultaneously both variables have a significant effect on employee performance with a sig value of 0.00 < 0.05.